A prospective randomised simulation trial comparing our novel AIR-BOX to standard airway equipment storage modalities. (28th October 2020) - Piechowski, Wojciech; Clapper, Timothy C; Park, Joel C; Ching, Kevin; St. George, Jonathan
Abstract : Background: There is little evidence guiding equipment handling during emergency endotracheal intubations (EEI). Available evidence and current practice are either outdated, anecdotal or focused on difficult—not emergency—intubation. In this study, we describe and evaluate our equipment handling unit: the AIR-BOX. Methods: This is a proof-of-concept, prospective, randomised simulation trial. A convenience sample of 50 airway course participants voluntarily underwent randomisation: 21 to the AIR-BOX group, 14 to the intubation box group, and 15 to the crash cart group. The volunteers were asked to intubate a manikin using the equipment from the storage unit of their randomisation. Outcome measures included time-to-readiness, time-to-intubation, first-pass success, and subjective operator experience. Results: The mean time-to-readiness was 67.2 s with the AIR-BOX, 84.6 s with the intubation box, and 115 s with the crash cart. The mean time-to-intubation was 105 s with the AIR-BOX, 127 s with the intubation box and 167 s with the crash cart. A statistically significant difference was achieved between the AIR-BOX and the crash cart. No statistically significant difference was found between the three groups with regard to first-pass success or the time between intubation readiness and intubation. Conclusions: This study supports the AIR-BOX as a viable tool that can improve and simplify access to emergency intubating equipment. It also opens doors for multiple future innovations that can positively impact equipment handling practices. Future studies can focus on assessing whether applying the AIR-BOX will yield a clinically significant impact on patient outcomes.